Linguistic Turn and Postmodernity - García-Lorente, José Antonio (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This article attempts to show how postmodernity comes from doctrines originating in the «linguistic revolution». The thinkers of the 19th century German tradition —who are included in the socalled «Triple-H theory»— wanted to shift the line of argument from reason to language. The presupposition of the primacy of language will be presumed by the prophet of postmodernism, Nietzsche, thus making possible the dawning of postmodernity. Postmodernity will accept unquestionably the shift from the universal and absolute to the particular and relative.